Stepped-care versus therapist-guided, internet-based cognitive behaviour therapy for childhood and adolescent anxiety: A non-inferiority trial - Sonja March; Susan H Spence; Larry Myers; Martelle Ford; Genevieve Smith; Caroline L Donovan (Internet Interventions, 2023)
Objective: This preregistered randomized trial examined whether a stepped-care approach to internet-delivered cognitive behaviour therapy (ICBT-SC) is non-inferior to therapist-guided ICBT (ICBT-TG) for child and adolescent anxiety. Method: Participants were 137 Australians, aged 8–17 years (56 male), with a primary anxiety disorder. This randomized, non-inferiority trial compared ICBT-SC to an evidence-based, ICBT-TG program with assessments conducted at baseline, 12 weeks and 9-months after treatment commencement. All ICBT-SC participants completed the first 5 online sessions without therapist guidance. If they responded to treatment in the first 5 sessions (defined as reductions of anxiety symptoms into non-clinical range), they continued without therapist guidance for the final 5 sessions. If they did not respond to treatment in the first 5 sessions, the final five sessions were supplemented with therapist-guidance (through email). All ICBT-TG participants received therapist guidance (email) after each session, for all 10 sessions. Measures included clinical diagnostic interview (severity rating as primary outcome), as well as parent and child reported anxiety and anxiety-related interference (secondary outcomes). Results: ICBT-SC was found to be non-inferior to ICBT-TG on primary and secondary outcomes, according to clinician, parent and young person report at 12-weeks and 9-months. Treatment satisfaction was moderate to high for both conditions. Significant clinical benefits were evident for participants in both treatments. Of participants who remained in the study, 77 % (50.7 % ITT) of ICBT-SC and 77 % (57.1 % ITT) of ICBT-TG were free of their primary anxiety diagnosis by 9-month follow-up, with no differences between conditions. Conclusion: A stepped-care ICBT approach for clinically anxious children and adolescents may offer an acceptable treatment model that can increase access to evidence-based treatment.